Western Law and Communist Dictatorship - Forte, David F (1983)
To erect an order that can withstand such an attack, all appropriate and legitimate legal resources should be employed. First, individual acts of terror, by whomsoever committed, should be punished, first of all, by municipal criminal legislation. This municipal law should be strengthened by conventions and treaties requiring prosecution or extradition. Second, in addition to individual culpability fastened on soldiers who commit acts of terror, all legitimate responses in international law should be employed by and against the responsible state, including protest, diplomacy, and disciplinary mechanisms. Where the responsible state actually sponsors such actions, retorsion and reprisal should be considered, particularly when a sponsoring state, such as Libya, has egregiously violated the laws of war. Third, the United States should never accept, expressly or impliedly, any of the legal and political mechanisms of the United Nations, or other bodies, that legitimize terroristic groups. Finally, in treating those groups in and of themselves and apart from the legal responsibility of their state sponsors, the United States should concretize the emerging norm of hostis humanis generis, that is, the universal criminality of those groups whose acts of terror are primary, habitual, and essential to their political program. These groups have become overt enemies of the political, moral and legal integrity of our world order. They should be recognized as such